The Use of Creative Drama with Acting-Out Sixth and Seventh Grade Boys and Girls - Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes the development and use of creative drama with 30 children over a six month period. The children were seen weekly for half hour sessions in groups of 7 or 8. They were asked to create a short drama or play which was then video-taped and immediately played back for discussion. Overtime, the dramas evolved through four stages: chaos; control and chaos; control;and flexibility. Certain developmental and psychological themes also emerged.These were: narcissism and exhibitionism, activity, orality, dominance, morality, social themes, comedy and rhythm. These findings are discussed both from Freudian and Piagetian frameworks and several implications are raised.